Abundance of early life stages of the surf silverside Notocheirus hubbsi (Teleostei, Atheriniformes) in the coastal nearshore of central Chile - Zavala-Muñoz, Francisca; Landaeta, Mauricio F.; Bernal-Durán, Valentina; Bustos, Claudia A.; Dyer, Bryan S. (Revista de Biología Marina y Oceanografía, 2021)
The abundance of early stages of the surf silverside Notocheirus hubbsi in nearshore waters of central Chile, collected in samplings set up to assess the lunar cycle during austral spring and summer is reported. A total of 19 specimens were collected with light traps, 16 larvae (7.89-16.20 mm SL) in austral spring and 3 juveniles (30.70-34.60 mm SL) in summer. Capture per unit effort (CPUE) varied from 0.33 to 2.00 ind. light trap-1 night-1 during the entire study period (September 2015-February 2016, and September 2016-February 2017). N. hubbsi catches recorded maximum abundance during the new moon and no catches during full moon.